Colonialism, ethnicity, and geopolitics in the development of the Singapore National Library - Luyt, Brendan (2012)
This article addresses three key social, political, and economic forces that influenced the development of the Singapore National Library in the 1950s and 1960s. Singapore inherited a British colonial system that neglected both the education of indigenous residents and library development. A major impetus for the development of a national library came as the country moved toward independence in the 1950s and 1960s and it became politically necessary to provide a multilingual rather than a predominantly English-language library. After independence the Singapore National Library collections and policies were influenced by the censorship imposed by the government in power in the early 1960s. This article examines these three social factors—colonial inheritance, ethnic issues, and the geopolitical situation—and the effects they had on the early development of the Singapore National Library.